(untitled) (Journal of Energy and Safety Technology (JEST), 2025)
A good power quality is crucial to avoid any disruptions or damages to equipment, especially sensitive equipment as most consumers in the industrial sector, utilities, residential, and commercial use a lot of modern technology and devices. The power quality issues that the consumer faced are voltage sag, voltage swell, flickering, fluctuations, and more. This project will focus on voltage sag as it is the most common issue in modern distribution systems. Some causes of these issues are unavoidable, as weather conditions are also one of the factors that contribute to voltage sags. For instance, lightning, storms, heavy rain, and more. Besides equipment failure, consumers could also face an increase in electricity bills, wasted energy, communications interference, and disruption of the whole system. Thus, an effective device or method is needed to mitigate voltage sag. A modelling of Dynamic Voltage Restorer (DVR) and Distribution Static Compensator (DSTATCOM) is done in MATLAB/Simulink to simulate the comparison of effectiveness between two devices. The three-phase test model represents the typical distribution system, incorporating three phase source, step-down transformers, transmission line, and two types of loads, which are inductive load and capacitive load. The simulation is done under three-phase fault, double line-to-ground fault, and single line-to-ground fault. From the analysis of voltage recovery, THD improvement, and power injection, it is proven that DVR is much superior in mitigating voltage sag than DSTATCOM.